2017
DOI: 10.1002/rra.3187
|View full text |Cite
|
Sign up to set email alerts
|

Swimming behaviour and ascent paths of brook trout in a corrugated culvert

Abstract: Culverts may restrict fish movements under some hydraulic conditions such as shallow flow depths or high velocities. Although swimming capacity imposes limits to passage performance, behaviour also plays an important role in the ability of fish to overcome velocity barriers. Corrugated metal culverts are characterized by unsteady flow and existence of low‐velocity zones, which can improve passage success. Here, we describe swimming behaviour and ascent paths of 148 wild brook trout in a 1.5‐m section of a corr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 25 publications
0
14
0
Order By: Relevance
“…These fish shared traits typical of a strong ability to accelerate and reach high swimming speeds, such as a streamlined body and a short caudal peduncle (Webb, ). However, four of the six studied culverts were made of corrugated metal, which creates low‐velocity areas inside the pipes and allows fish to rest during ascents (Goerig, Bergeron, & Castro‐Santos, ; Goerig et al, ). This factor may have partially offset the negative effect of water velocity on passage success and may explain why morphological traits associated with higher swimming ability did not have even greater impact on passage success.…”
Section: Discussionmentioning
confidence: 99%
“…These fish shared traits typical of a strong ability to accelerate and reach high swimming speeds, such as a streamlined body and a short caudal peduncle (Webb, ). However, four of the six studied culverts were made of corrugated metal, which creates low‐velocity areas inside the pipes and allows fish to rest during ascents (Goerig, Bergeron, & Castro‐Santos, ; Goerig et al, ). This factor may have partially offset the negative effect of water velocity on passage success and may explain why morphological traits associated with higher swimming ability did not have even greater impact on passage success.…”
Section: Discussionmentioning
confidence: 99%
“…Developing low‐velocity regions to improve fish passage and provide habitat for fish in energetically taxing environments has gradually become a predominant restoration strategy (Ead et al, ; Goerig et al, ; Newbold & Kemp, ; Watson, Goodrich, Cramp, Gordos, & Franklin, ). The occupation of low‐velocity regions by fish is well supported here and consistent with the literature (Goodrich, Watson, Cramp, Gordos, & Franklin, ; Johnson, Pearson, Southard, & Mueller, ; Rodgers et al, ; Watson et al, ), which has verified that exploiting low‐velocity regions in the upstream passage can provide resting areas for fish when they experience fatigue, so as to accumulate energy to complete the passage.…”
Section: Discussionmentioning
confidence: 99%
“…Large woody debris, which can increase flow depth and decrease flow velocity, was adopted as a modification to restore fish habitat (Bocchiola, ; Zika & Peter, ). Corrugated culverts are regarded as effective and ubiquitous structures for improving upstream fish passage (Ead, Rajaratnam, Katopodis, & Ade, ; Goerig, Bergeron, & Castro‐Santos, ; Newbold & Kemp, ) because the corrugations can create large low‐velocity areas that shield fish. Furthermore, when placed in a heterogeneous flow field created by hemispherical boulders, guppies ( Poecilia reticulata ) quickly respond to velocity and turbulence characteristics and exhibit variation in swimming behavior (Hockley, Wilson, Brew, & Cable, ).…”
Section: Introductionmentioning
confidence: 99%
“…Several physical studies indicated that large roughness elements, corrugations and baffles may effectively assist the upstream passage of fish (Gigleux & de Billy, 2013; Macdonald & Davies, 2007; Olsen & Tullis, 2013; Santos et al, 2021). A few biological studies under controlled conditions at full‐scale showed that small to medium‐size fish tended to follow paths along low‐velocity zones (LVZs) (Goerig, Bergeron, & Castro‐Santos, 2017; Pearson et al, 2005), as previously reported in box culverts (Blank, 2008; Cabonce, Fernando, Wang, & Chanson, 2019; Cabonce, Wang, & Chanson, 2018; Jensen, 2014; Wang, Chanson, Kern, & Franklin, 2016).…”
Section: Introductionmentioning
confidence: 99%